THE ROLE OF VALUE ADDED TAX IN THE FORMATION OF BUDGET REVENUES, USING THE EXPERIENCE OF FOREIGN COUNTRIES - Urazmatov Jonibek Musurmanovich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Objective: This study aims to assess the role of Value-Added Tax (VAT) in the fiscal policy of Uzbekistan, focusing on its contribution to state budget revenues, comparing it with VAT systems in Italy and the Russian Federation, and identifying strategies for improving VAT administration through reforms and digital technologies. Methods: A comparative analysis was conducted using quantitative methods, analyzing VAT data from Uzbekistan, Italy, and the Russian Federation from 2017 to 2023. Key indicators such as the share of VAT in budget revenues and tax elasticity were used to evaluate the dynamic effectiveness of VAT collection. Data sources included government reports and international financial institutions. Results: The results show that Uzbekistan’s VAT revenue share in the budget is higher than that of Italy and Russia, with notable fluctuations across the years. Uzbekistan's systemic reforms have emphasized modernizing tax systems and reducing the shadow economy, leading to a more efficient tax collection process through digital technologies. Novelty: The study highlights the importance of VAT reforms in Uzbekistan, proposing a strategic framework to modernize VAT administration, including improved tax rates, legal procedures, and inter-budgetary distributions. This research contributes new insights into optimizing VAT systems in transitional economies, particularly in the context of digitalization and tax efficiency.